WILDCARD MASK SEBAGAI FILTERING IP ADDRESS MENGGUNAKAN METODE ACCESS LIST CONTROL PADA ROUTER CISCO - Aziz Setyawan Hidayat (Universitas Bina Sarana Informatika, 2017)
Implementation of a firewall in the computer network is important. In national newspapers proclaiming dated May 12, 2015 that Indonesia's second largest order of Origin Cyber Crime in the World. Furthermore, a report issued in 2014 the period of January to Desmber by Indonesia Security Incident Response Team on Internet Infrastructure / Coordination Center (id-SIRTII) that there was an attack ± 350,000 times in May in the form of an exploit. Exploit code is a computer security attack specifically. Exploit widely used for penentrasi either legally or illegally to find the weaknesses (Vulnerability) on the destination computer. Web attacks and attack-misc at its peak in August as much as ± 41,000 times. The first step to anticipate the occurrence of such attacks is a firewall application. Implementation firewall one of them by utilizing the Cisco Router. Cisco Router in the device that applies the concept of Access Control List (ACL) and included some content, such as: Application wildcard mask, specify the source IP address, destination IP address and define the final data package.Keyword—Firewall, Access Control List, the Destination IP Address, Wildcard Mask.